Pentingnya Mengetahui Golongan Darah Anda: Dampaknya pada Kesehatan dan Kehidupan Sehari-hari - Tyara Avrilyanti Ghea Indriansyah; Karina Sella Juwitasari; Margaretha Alesandria Natasya Weka; Pramesti Listanto; Latifa Alya Khairunnisa; Juwita Ramadhani Octavianingrum; Liss Dyah Dewi Arini (STIKes Ibnu Sina Ajibarang, 2025)
Knowledge of one’s blood type plays a crucial role in supporting individual health and preparedness in medical emergencies. This literature review explores the relationship between the ABO and Rhesus blood group systems and various health outcomes, including susceptibility to infections, cardiovascular risks, and biochemical implications in personalized medicine. Based on a synthesis of ten scholarly sources, the findings reveal that blood type influences vulnerability to COVID-19, gastrointestinal infections, and elevates cardiovascular disease risk particularly among non-O blood types. These results emphasize the importance of early education and blood type screening as preventive measures. The study also highlights the need for integrating blood type data into national health care systems.